2008
DOI: 10.3168/jds.2007-0781
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prepartum Dietary Carbohydrate Source and Monensin on Periparturient Metabolism and Lactation in Multiparous Cows

Abstract: Eighty-five multiparous Holstein cows were used in a completely randomized design with restrictions to evaluate the effects of prepartum carbohydrate (CHO) source and monensin on periparturient dry matter intake (DMI), blood parameters, and lactation performance of dairy cows. Dietary treatments were arranged in a 2 x 2 factorial arrangement with a conventional (CONV) dry cow diet and a nonforage fiber source (NFFS) dry cow diet not supplemented (-) or supplemented (+) with 330 mg/cow per d of monensin as a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
7
0
5
Order By: Relevance
“…For example, Smith et al (2005) observed the daily DMI of 13.7 kg/head when feeding the ration with a low level of NFC (34%) and 13.8 kg per head when using the FR with a high level of NFC (40%). However, other authors (Grum et al, 1996;Holcomb et al, 2001;Keady et al, 2001;Rabelo et al, 2003;Chung et al, 2008) found differences in DMI in their experiments. In these studies, higher DMI was always associated with the FR containing higher levels of NFC.…”
Section: Dry Matter Intakementioning
confidence: 62%
“…For example, Smith et al (2005) observed the daily DMI of 13.7 kg/head when feeding the ration with a low level of NFC (34%) and 13.8 kg per head when using the FR with a high level of NFC (40%). However, other authors (Grum et al, 1996;Holcomb et al, 2001;Keady et al, 2001;Rabelo et al, 2003;Chung et al, 2008) found differences in DMI in their experiments. In these studies, higher DMI was always associated with the FR containing higher levels of NFC.…”
Section: Dry Matter Intakementioning
confidence: 62%
“…NFC) [23], as observed by Inácio et al [24] who tested differ ent concentrate levels for heifers fed sugarcane bagasse as an exclusive roughage source. On the other hand, Chung et al [25] relate the increase in nutrients intake to the higher physical density of the concentrate by the decrease in the size of the particles in relation to the roughage. The main effects are the augmentation of the passage rate of the digesta through the gastrointestinal tract, making the increase in the consumption possible.…”
Section: Resultsmentioning
confidence: 99%
“…Moreira et al (2015), estudando o período de transição de vacas, encontrou a maior concentração no quinto dia após o parto. Os resultados desse metabólito, encontrado neste trabalho, em média variou entre 0,34±0,11mmol/L a 0,56±0,21mmol/L no G1 e 0,37±0,09mmol/L a 0,65±0,20mmol/L no G2, resultados semelhantes aos descritos por Chung et al (2008), Moreira et al (2015) e Alvarenga et al (2015) realizados durante o final da gestação e início da lactação, os dois últimos autores trabalharam com vacas leiteiras mestiças (holandês x Gir), semelhante a esta pesquisa. Este corpo cetônico é o parâmetro bioquímico de maior confiabilidade devido a sua estabilidade, quando encontrado em concentrações elevadas demostra quadro de déficit energético grave (Castro et al 2008).…”
Section: Discussionunclassified